Anteseden Dan Konsekuensi Dari Consumer Engagement Kepada Brand Love Pada Smartphone Di Indonesia - Bhatara Febryanto; Fatik Rahayu; Robert Kristaung (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This research aims to test and analyze the influence of brand relationship quality, consumer community identification, brand familiarity with consumer engagement and brand love on consumers who use online digital applications in a mobile phone brand. The sample used in this research was 210 respondents. The sampling technique used was purposive sampling. Data were analyzed using the Structural Equation Model (SEM) method. The results of this research are: (1) Brand Relationship Quality has a positive effect on Consumer Engagement, (2) Consumer Community Identification has a positive effect on Consumer Engagement, (3) Brand Familiarity has a positive effect on Consumer Engagement, (3) Consumer Engagement has a positive effect on Brand Love.